Editorial Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Yahaya, Mohamad Hafiz; Taharuddin, Nurul Shima; Md Nazri, Haslinda; Rosman, Muhammad Redza; Nazrin, Nizar (Idealogy Journal; Vol 6 No 1 (2021): Idealogy Journal (April 2021), 2021)
We are extremely excited to announce our Idealogy Journal of Arts and Social Science for its 6th volume and 1st issue. The journal allows academicians to publish interventions and viewpoints on arts and social sciences field that are interest to the academic community and are likely to spark a vibrant discussion among the journal's readers about various perspectives. The close relationship with Indonesia, Pakistan, Saudi Arabia, Bangladesh and other countries has been invested. As a result of which, we received outstanding quality papers of research.